A diet enriched in linoleic acid compromises the cryotolerance of embryos from superovulated beef heifers - Guardieiro, Monique M.; Machado, Grazieli M.; Bastos, Michele R. [UNESP]; Mourao, Gerson B.; Carrijo, Luiz H. D.; Dode, Margot A. N.; Leroy, Jo L. M. R.; Sartori, Roberto (CSIRO Publishing, 2014)
Dietary rumen-protected fat rich in linoleic acid may affect the superovulatory response and embryo yield; however, its effects on in vivo embryo cryotolerance are unknown in zebu cattle. The present study evaluated the production and cryotolerance after freezing or vitrification of embryos from Nelore heifers supplemented with rumen-protected polyunsaturated fatty acids (PUFA). Forty heifers kept in pasture were randomly distributed into two groups according to the type of feed supplement (F, supplement with rumen-protected PUFA, predominantly linoleic; C, control fat-free supplement with additional corn). Supplements were formulated to be isocaloric and isonitrogenous. Each heifer underwent both treatments in a crossover design with 70 days between replicates. After 50 days feeding, heifers were superovulated. Embryos were evaluated morphologically and vitrified or frozen. After thawing or warming, embryo development was evaluated in vitro. There was no difference between the F and C groups (P > 0.10) in terms of embryo production. Regardless of the cryopreservation method used, Group C embryos had a greater hatching rate after 72 h in vitro culture than Group F embryos (44.3 +/- 4.2% (n = 148) vs 30.9 +/- 4.0% (n = 137), respectively; P = 0.04). Moreover, vitrified and frozen embryos had similar hatching rates (P > 0.10). In conclusion, dietary rumen-protected PUFA rich in linoleic acid did not improve embryo production and compromised the cryotolerance of conventionally frozen or vitrified embryos from Nelore heifers.
Keywords: cryopreservation, fatty acid, nutrition.